Analisis Keputusan Pembelian BTS Meal: Tinjauan Pemilihan Produk, Merek, Penyalur, Kuantitas Pembelian, Waktu Pembelian, dan Metode Pembayaran - Mamun Sutisna; Ira Siti Sarah (Jurnal Riset Bisnis dan Investasi, 2022)
On May 26, 2021, fans of the idol group BTS were surprised by McDonald's which innovated by collaborating with the famous South Korean boy band by launching the "BTS Meal" product. The euphoria of the presence of the BTS Meal was quite horrendous and led to the closing of McDonald's outlets in several places. This study aims to analyze the purchasing decisions of BTS Meal in Bandung. The study used quantitative methods with a total sample of 200 people taken using the purposive method. The data were analyzed using descriptive analysis, regression analysis and T test. The results showed that respondents gave high ratings on several aspects of BTS Meal products such as product selection, brand, and distributor. Furthermore, product selection, brand, dealer, purchase quantity, time of purchase, and payment method also have a significant positive effect on purchasing BTS Meal in Bandung City.